2016
DOI: 10.1021/acs.jchemed.6b00320
|View full text |Cite
|
Sign up to set email alerts
|

Scaffolded Semi-Flipped General Chemistry Designed To Support Rural Students’ Learning

Abstract: Students who lack academic maturity can sometimes feel overwhelmed in a fully flipped classroom. Here an alternative, the Semi-Flipped method, is discussed. Rural students, who face unique challenges in transitioning from high school learning to collegelevel learning, can particularly profit from the use of the Semi-Flipped method in the General Chemistry classroom. This method brings together preparation before class, active learning in class, and a supportive homework system, and it appears to have significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 19 publications
0
21
1
Order By: Relevance
“…Over the last few years, there has been an increase in literature presenting the design, implementation, effectiveness, and students' attitudes of flipped classroom and blended learning as an active learning teaching method for general chemistry and organic chemistry in large and small class sizes (e.g., Bernard et al, 2017;Christiansen, 2014;Eichler & Peeples, 2016;Fautch, 2015;Flynn, 2015;He et al, 2016;Hibbard et al, 2016;Lenczewski, 2016;Mooring, et al, 2016;Naibert et al, 2020;Reid, 2016;Rossi, 2015;Ryan & Reid, 2016;Seery, 2015;Shattuck, 2016;Smith, 2013;Weaver & Sturtevant, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the last few years, there has been an increase in literature presenting the design, implementation, effectiveness, and students' attitudes of flipped classroom and blended learning as an active learning teaching method for general chemistry and organic chemistry in large and small class sizes (e.g., Bernard et al, 2017;Christiansen, 2014;Eichler & Peeples, 2016;Fautch, 2015;Flynn, 2015;He et al, 2016;Hibbard et al, 2016;Lenczewski, 2016;Mooring, et al, 2016;Naibert et al, 2020;Reid, 2016;Rossi, 2015;Ryan & Reid, 2016;Seery, 2015;Shattuck, 2016;Smith, 2013;Weaver & Sturtevant, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are conflicting results presented in recent literature on the student attitudes towards a flipped chemistry classroom. However, papers presenting the positive effects on students (Chase et al, 2013;Eichler & Peeples, 2016;Hemraj-Benny & Beckford, 2014;Hibbard et al, 2016;Lenczewski, 2016;Mooring et al, 2016;Oliver-Hoyo & Allen, 2005;Ryan & Reid, 2016;Trogden, 2015;Weaver & Sturtevant, 2015) either in performance and/or student attitudes with respect to learning progress, confidence, and motivation outnumber the papers presenting the negative attitudes or learning experiences (He et al, 2016) or demonstrating no significant improvement in student performance compared to those taught by traditional lectures (Christiansen, 2014;Rein & Brookes, 2015). The studies that found no significant improvement, however, have found that there may be improvements to student confidence and enthusiasm (Chase et al, 2013;Hemraj-Benny & Beckford, 2014;Oliver-Hoyo & Allen, 2005;Rau et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Most incorporate some type of groupwork, 22−34 and several use minilectures or just-in-time teaching to provide clarification on concepts when needed. 10,13,20,[22][23][24][25]27,[30][31][32][33]35 Some provide additional time for these activities by adopting a hybrid structure where students participate in active learning during a specific block of time or day of class. [7][8][9][10]18,30 Regardless of the type of F2F learning environment, flipped classes are structured such that students enter the classroom with some level of understanding, which they build upon during class time.…”
Section: Structure Of Flipped Learning Environmentsmentioning
confidence: 99%
“…Higher-education flipped chemistry classrooms include a variety of different F2F active learning environments, such as peer-led team-learning (PLTL), process-oriented guided-inquiry learning (POGIL), , or other combinations of peer instruction, problem-based learning, and/or think–pair–share type exercises. , In addition, some classes incorporate case studies , or whole-class discussions into their class time. Most incorporate some type of groupwork, and several use minilectures or just-in-time teaching to provide clarification on concepts when needed. ,,, ,, , Some provide additional time for these activities by adopting a hybrid structure where students participate in active learning during a specific block of time or day of class. ,, …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation